2017
DOI: 10.1007/s10096-017-2960-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive score of haematological toxicity in patients treated with linezolid

Abstract: This score could help in the identification of patients with high risk for HT and assess the use of an antibiotic other than LZD, an important issue considering its relation with 30-day mortality observed in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Previous studies have also identified the presence of moderate or severe liver diseases as a risk factor for developing hematological toxicity (20,(29)(30)(31). In the same way, lactic acidosis has proven to be more common in patients with liver impairment (32).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also identified the presence of moderate or severe liver diseases as a risk factor for developing hematological toxicity (20,(29)(30)(31). In the same way, lactic acidosis has proven to be more common in patients with liver impairment (32).…”
Section: Discussionmentioning
confidence: 97%
“…The way thrombocytopenia is defined may partly explain this disparity. We defined it as a reduction in platelet counts ≥ 30% from baseline and a value ≤ 150,000 cells/µL while other studies considered a decrease of 25% in platelet counts [ 25 ] or a decrease in platelet counts ≥ 50% from baseline [ 17 ]. The reasons why this prevalence is more than 20 times higher than that reported in the SmPC are possibly related to the high proportion of patients presenting associated risk factors in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure has already been described as a risk factor in previous studies [ 14 , 15 , 16 , 17 , 37 ]. Our cut-off value for renal failure was 60 mL/min as in Hanai’s [ 15 ] and Nukui’s [ 16 ] studies, but others described lower values, between 30 and 50 mL/min [ 14 , 25 , 38 ]. The renal function is also included in the Charlson index, but based on serum creatinine levels, with a cut-off value set at 3 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic impairment, however, was a significant risk factor associated with thrombocytopenia in both the general population and the subgroup analysis, which warrants further investigation into the role that hepatic metabolism may play in the mechanism of LAT. 14…”
mentioning
confidence: 99%